2020
DOI: 10.21203/rs.3.rs-47413/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Recurrent Dislocation and Dissociation of Bipolar Cup: Two Intricate Cases and Review of Literature.

Abstract: Background: Bipolar hemiarthroplasty (BHA) is one of the best options to treat femoral neck fracture in elderly patients. However, the early dislocation problem also happens in the bipolar cup. Furthermore, BHA has a specific implant-related complication, namely bipolar cup dissociation, in which the femoral head dissociates from the polyethylene (PE) liner. Early dislocation and dissociation are relatively uncommon but devastating complications and almost always lead to reoperation with revision of the prosth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Moriarity et al [9] stated that the dislocated hip HA should be managed by open reduction and be converted to cemented THA. This study was supported by Fan et al, who performed revision surgery of BHA to THA with dual mobility cups, which showed an excellent postoperative result [10].…”
Section: Discussionsupporting
confidence: 66%
“…Moriarity et al [9] stated that the dislocated hip HA should be managed by open reduction and be converted to cemented THA. This study was supported by Fan et al, who performed revision surgery of BHA to THA with dual mobility cups, which showed an excellent postoperative result [10].…”
Section: Discussionsupporting
confidence: 66%